(untitled) (Research, Society and Development, 2019)
The management of solid waste corresponds to the necessary procedures for the management of these materials, involving the stages of non-generation of waste, reduction, reuse, recycling, treatment and final disposal. In this context, this work aimed to analyze the generation and destination of solid urban waste in the city of Itabira (MG) in the years 2016 and 2017. The methodology used was based on the analysis of documents provided by the Development Company of Itabira Ltda. (ITAURB) containing data on the quantities of municipal solid waste collected, recyclable waste and waste destined for the landfill. From the data obtained, due to the increase of dwellings and inhabitants, there was a growth of 1.9% in the collection of solid urban waste between the years 2016 and 2017 and of 6.6% in the solid waste recycling in this period. In addition, it was possible to notice an increase of approximately 1% of the waste sent to the landfill. The importance of research for the analysis of urban solid waste generation and the destination of these was highlighted, seeking solutions to minimize the negative environmental, social and economic impacts triggered by these materials.